The Occurrence or Fibrillary Glomerulonephritis in Patients with Diabetes Mellitus May Not Be Coincidental: A Report of Four Cases - Fayna González-Cabrera; Fernando Henríquez-Palop; Ana Ramírez-Puga; Raquel Santana-Estupiñán; Celia Plaza-Toledano; Gloria Antón-Pérez; Silvia Marrero-Robayna; Davinia Ramírez-Medina; Roberto Gallego-Samper; Nicanor Vega-Díaz; Rafael Camacho-Galan; José C. Rodríguez-Pérez (Case Reports in Medicine)
Although clinical presentation of fibrillary glomerulonephritis is similar to most forms of glomerulonephritis, it is usually difficult to make the diagnosis. Clinical manifestations include proteinuria, microscopic haematuria, nephrotic syndrome, and impairment of renal function. A diagnosis of fibrillary glomerulonephritis is only confirmed by renal biopsy and it must comprise electronmicroscopy-verified ultrastructural findings. We report four cases between 45–50 years old with documented type 2 diabetes mellitus (T2DM) and arterial hypertension. All patients were found to have fibrils on kidney biopsy. The differential diagnosis of fibrils in the setting of diabetes mellitus is also discussed.